2011
DOI: 10.1371/journal.pgen.1002126
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Analysis of Parent-of-Origin Allelic Expression in the Arabidopsis Endosperm

Abstract: Genomic imprinting is an epigenetic phenomenon leading to parent-of-origin specific differential expression of maternally and paternally inherited alleles. In plants, genomic imprinting has mainly been observed in the endosperm, an ephemeral triploid tissue derived after fertilization of the diploid central cell with a haploid sperm cell. In an effort to identify novel imprinted genes in Arabidopsis thaliana, we generated deep sequencing RNA profiles of F1 hybrid seeds derived after reciprocal crosses of Arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
387
2
1

Year Published

2012
2012
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 241 publications
(412 citation statements)
references
References 68 publications
22
387
2
1
Order By: Relevance
“…Deep sequencing of mRNA libraries derived from reciprocal intraspecific crosses of Arabidopsis thaliana, rice, and maize has proven to be an effective strategy to identify genes that are preferentially expressed from one parental allele during seed development [4][5][6][7][8][9]. These studies have confirmed that imprinting is mostly endosperm-specific and have significantly expanded the number of imprinted genes to between about 50-200 in each species.…”
Section: Genomic Studies Of Imprintingmentioning
confidence: 99%
See 4 more Smart Citations
“…Deep sequencing of mRNA libraries derived from reciprocal intraspecific crosses of Arabidopsis thaliana, rice, and maize has proven to be an effective strategy to identify genes that are preferentially expressed from one parental allele during seed development [4][5][6][7][8][9]. These studies have confirmed that imprinting is mostly endosperm-specific and have significantly expanded the number of imprinted genes to between about 50-200 in each species.…”
Section: Genomic Studies Of Imprintingmentioning
confidence: 99%
“…While the cause is still unknown, partial imprinting might be a reflection of past conflict between alleles (kinship theory) [12] or of a dosage balance, as in the case of transcriptional regulators functioning as part of macromolecular complexes [13]. Imprinting can also be specific to particular strain [6], further highlighting the need to assess imprinting in multiple genetic backgrounds within a species.…”
Section: Genomic Studies Of Imprintingmentioning
confidence: 99%
See 3 more Smart Citations